PEMBELAJARAN MODEL PROBLEM BASED LEARNING BERORIENTASI PROFIL PELAJAR PANCASILA SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR IPAS KELAS IV SD - Atmaja, Adi Tri; Niam, Fathul; Zamroji, Nanang (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
This study aims to improve the learning outcomes of IPAS material on the form of substances through the Problem-Based Learning learning model oriented to the Pancasila student profile in class IV. The research subjects were 27 consisting of 16 boys and 11 girls. Using a qualitative descriptive approach with a class action research method, which was carried out in two cycles. Data analysis using a Likert scale with an increase in the average percentage of class completeness. The results of this study were obtained in the first cycle, 81.8% of students (22 out of 27) achieved scores above 75, with a range of scores between 70 to 83, there were 18.2% of students (5) who had not reached the passing standard. Cycle 2, 92.6% of learners (25 out of 27) achieved a score above 75, 51.9% of learners (14) scored 80 and above. Achievements in cycles I and II show that the application of the PBL model oriented to the Pancasila learner profile has succeeded in improving the quality of learning as seen from the significantly improved learning outcomes.